GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN (Studi Empiris pada BUMN di Indonesia): (Studi Empiris pada BUMN di Indonesia) - Megawati, Happy (Media Akuntansi dan Perpajakan Indonesia, 2021)
This study aims to examine the effect of good corporate governance on financial performance. The independent variable in this study is good corporate governance which is proxied as board of directors, board of independent commissioners, audit committees, managerial ownerships, and institutional ownerships, while the dependent variable of this study is financial performance which proxied as return on assets (ROA). The sample used in this study were 24 state-owned companies listed on IDX for the 2015–2019 period. The sampling method used is non-probability sampling. This study uses secondary data in the form of annual reports for the 2015– 2019 period which obtained from the company’s official website. The data collected were then analyzed by multiple linear regressions using SPSS 25. The results of this study show that board of independent commissioners have negative effects on ROA. This means that the greater the number of board independent commissioners, the lower the ROA will be. The results also show that other independent variables, namely board of directors, audit committees, managerial ownerships, and institutional ownerships have no effect on ROA.